Social Determinants of Health in The Maritim Sector: A Qualitative Analysis of The Role of Safety Culture And Leadership on The Health and Performance of Stevedores at Tanjung Perak Port - Saktyawan Dwiki Pamungkas; Ramadhan Hasri Harahap; Mauritz Hm Sibarani (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
This qualitative study investigates the critical influence of workplace culture and leadership styles on occupational health and safety (OHS) outcomes for stevedores at Tanjung Perak Port, Indonesia. Framed within the public health concept of social determinants of health, the research employed a phenomenological approach, conducting in-depth interviews with ten stevedores to capture their lived experiences. Thematic analysis revealed a pervasive normalization of risk, where a culture of machismo and fear of reprisal led to the under-reporting of hazards and the acceptance of unsafe practices as an inevitable part of the job. A stark dichotomy in leadership emerged as a pivotal factor, distinguishing between transactional "Boss" figures who prioritized production targets and fostered silence, and transformational "Leaders" who engendered psychological safety, open communication, and proactive problem-solving. The findings demonstrate that effective leadership is the primary lever for mitigating a negative safety culture, directly impacting both worker well-being and operational performance. The study concludes that sustainable port efficiency and resilience are contingent upon a safe and healthy workforce, necessitating a strategic shift from technical compliance alone towards interventions that cultivate positive safety cultures and develop transformative leadership at the supervisory level. This research provides a critical, human-centered evidence base for improving OHS policy and practice in the maritime sector and similar high-risk industries.